Interaction of Active MMIC with Package/Housing -Theory, Analysis and Measurement - Sarvaiya, A.; Gupta, S.; Ghodgaonkar, D. (Advanced Electromagnetics, 2014)
This paper presents enclosure effect comprehensive by 3D Electromagnetic modeling, simulation and measurement of active MMIC with Package/housing. When put inside a test box or package with a cavity, MMIC shows significant deviation from it RFOW measurement data. Cavity resonance’s adverse effects are analyzed by Eigen mode solver using CST Microwave Studio and RFOW measurement and in test box data is matched by simulating package/house with the best suited RF absorbers.